Encourage Healthy Indonesia Program through Improved Professional Competencies and Strengthening the Professionalism of Nurses in Sampang Regency – Madura - Laily Hidayati; Ninuk Dian Kurniawati; Abu Bakar; Achmad Tirmidzi; Hasanudin Hasanudin (Universitas Airlangga, 2019)
Introduction: Sampang is one of the districts in East Java that has many problems faced, especially in the health sector. With a population of 947,614 inhabitants, Sampang facing the issue of professionalism of health workers, nurses 'career paths, high prevalence of Tuberculosis, and high incidence ofdisasters (floods) in Sampang Regency that require nurses' readiness and ability in an emergency situation. Nurses as the frontline of health services are required to be able to demonstrate their professionalism through the effectiveness and success of the actions taken. This activity aimed to increase professionalism and encourage nurses to improve their competence through continuing education and training.Method: Faculty of Nursing Universitas Airlangga in collaboration with the Sampang Health Departement held conference and workshop on the topics: (1) nurse professionalism: assessment of legal aspects and nursing ethics; (2) nurse career paths; (3) comprehensive treatment of tuberculosis includes bio-psycho-socio-spiritual; (4) wound care; and (5) update on basic life support based on the 2015 AHA Guidelines. The target was 152 nurses at the primary health care in the working area of the Sampang District Health Office who are selected and identified according to the competencies. The activities were carried out during the period of July-August 2018.Result: A series of education and training programs produced output in the form of increasing knowledge and attitudes about nurse professionalism and career paths, increasing knowledge and attitudes about handling Tuberculosis patients, and increasing nurses' competence in wound care and BLS (Basic Life Support).Discussion: In the future, sustainable education and training activities are needed for nurses and other health workers in accordance with the latest developments in science and health technology to create professional nurses/health workers who encourage the achievement of the Healthy Indonesia program.